A Study on the Ability of the First Year Students of SMAN 10 Pekanbaru in Writing Recount Text - Khairunnisa Serenita Khairunnisa Serenita; Syafri K '; Erni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This descriptive research was aimed to find out the ability of the first year students of SMAN 10 Pekanbaru in writing recount text .The participants were 34 students. The data was collected by using writing tests. The students were given four topics and they were asked to choose only one. The research finding indicated that the students were capable in writing recount text although they still had difficulty in writing recount text based on the topic given. The result of test showed the average score of students writing ability was 60.27. It showed that the students were in average to good level and it means that the writing recount text based on the topic given was not too difficult for the students.Keywords:Recount Text, Writing Ability